Microfragmented Adipose Tissue Injection (MFAT) May Be a Solution to the Rationing of Total Knee Replacement: A Prospective, Gender-Bias Mitigated, Reproducible Analysis at Two Years. (10th June 2021) - Heidari, Nima; Borg, Tiffanie-Marie; Olgiati, Stefano; Slevin, Mark; Danovi, Alessandro; Fish, Brady; Wilson, Adrian; Noorani, Ali
Abstract : Background . Knee osteoarthritis (KOA) is a significant cause of disability in a globally ageing population. Knee replacement surgery has been shown to improve function and quality of life. Access to this intervention can be limited for a number of reasons including rationing of care, lack of healthcare provision in austere environments, and more recently, due to the cessation of elective orthopaedic care as a result of the COVID pandemic. Referral for knee replacement surgery is often guided by the patient's Oxford Knee Score (OKS). Recent therapies including treatment with microfragmented adipose tissue (MFAT) have emerged as alternatives to relieve pain and improve function in such patients. Method . We identified all patients with KOA Kellgren-Lawrence grade 3 and 4 in our dataset of patients treated with a single injection of MFAT and applied published OKS thresholds for referral for TKR to separate them into 3 cohorts according to their functional impairment. 220 patients (95 females, 125 males) with KOA were given one MFAT injection. The function (OKS) and quality of life (EuroQol-5) prior to and 24 months after therapy were compared. Results . MFAT injection provided a statistically significant improvement in the quality of life (EQ-5D) at 24 months in patients with a baseline OKS of 39 or less (p value: <0.001) as well as those with OKS of 27 or less who are deemed suitable for a knee replacement (p value: <0.001). Conclusion . MFAT injection improves quality of life in patients with KOA who are deemed suitable for the knee replacement. MFAT is a low-morbidity alternative biological treatment and can delay the need for total knee replacement in suitable patients.